Iran's Nuclear Program and the Global South - Onderco, M. author. aut Link
VIII, 107 p.
Keywords: This book studies the reactions of India, Brazil, and South Africa the three main non-proliferation actors of the Global South to Iran's nuclear program. Their responses are explained and situated in wider foreign policy context.